National targets for breastfeeding at hospital discharge have been achieved in Perth - Graham, Kathleen; Scott, Jane; Binns, Colin; Oddy, Wendy (Blackwells, 2005)
Aim: To report updated rates of breastfeeding in Perth through 2002/3 and to compare them to those from 1992/3. Methods: Design: A 12-mo longitudinal study. Setting: Two public maternity hospitals in Perth, Australia. Subjects: Eligible mothers of healthy newborn infants delivered between mid-September 2002 and mid-July 2003. Interventions: All eligible mothers were asked to participate in a 12-mo longitudinal study of infant feeding. While in hospital, participating mothers completed a questionnaire that included questions on how they were feeding their newborn. Main outcome measures: Prevalence of ever breastfeeding, and breastfeeding at discharge. Results: A total of 587 mothers, or 55% of those eligible, participated in the study. At hospital discharge, 93.8% of mothers in 2002/3 were breastfeeding compared with 83.8% in 1992/3. Significant increases were observed across all socio-demographic groups, with the biggest increase seen amongst younger mothers and those born outside of Australia.Conclusion: The national target of having in excess of 90% of mothers breastfeeding at discharge from hospital has been achieved in Perth. The challenge for health professionals and the community is to help maintain and further improve these breastfeeding practices.